2002
DOI: 10.1159/000071578
|View full text |Cite
|
Sign up to set email alerts
|

Overall DNA methylation and chromatin structure of normal and abnormal X chromosomes

Abstract: DNA methylation patterns were studied at the chromosome level in normal and abnormal X chromosomes using an anti-5-methylcytosine antibody. In man, except for the late-replicating X of female cells, the labeled chromosome structures correspond to R- and T-bands and heterochromatin. Depending on the cell type, the species, and cell culture conditions, the late-replicating X in female cells appears to be more or less undermethylated. Under normal conditions, the only structures that remain methylated on the X ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…This observation is consistent with a number of reports that have indicated that the overall levels of methylation on Xi are reduced relative to Xa and autosomes (Bernardino-Sgherri et al., 2002; Bernardino et al., 2000; Hellman and Chess, 2007; Viegas-Pequignot et al., 1988; Weber et al., 2005), and moreover that Xi is hypomethylated at intronic CpGs (Hellman and Chess, 2007; Lock et al., 1986). …”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with a number of reports that have indicated that the overall levels of methylation on Xi are reduced relative to Xa and autosomes (Bernardino-Sgherri et al., 2002; Bernardino et al., 2000; Hellman and Chess, 2007; Viegas-Pequignot et al., 1988; Weber et al., 2005), and moreover that Xi is hypomethylated at intronic CpGs (Hellman and Chess, 2007; Lock et al., 1986). …”
Section: Discussionsupporting
confidence: 93%
“…However, there is reason to question the association of cytosine methylation with facultative heterochromatin formation, as it has been recognized for some time that the inactive X chromosome in females is globally hypomethylated (Bernardino-Sgherri et al 2002), possibly related to the decreased methylation in bodies of genes (Hellman and Chess 2007) silenced as part of the X inactivation process.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…5 ). This situation might lead to functional mosaic aneusomy of some translocated genes and/or gene regulators in this region [ 32 , 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%